Controllable defect driven symmetry change and domain structure evolution in BiFeO3 with enhanced tetragonality. Issue 17 (15th April 2019) - Chen, Chao; Wang, Changan; Cai, Xiangbin; Xu, Chao; Li, Caiwen; Zhou, Jingtian; Luo, Zhenlin; Fan, Zhen; Qin, Minghui; Zeng, Min; Lu, Xubing; Gao, Xingsen; et al.
Abstract : True tetragonal BiFeO3 with c/a ratio of ∼1.3. Abstract : Defect engineering has been a powerful tool to enable the creation of exotic phases and the discovery of intriguing phenomena in ferroelectric oxides. However, the accurate control of the concentration of defects remains a big challenge. In this work, ion implantation, which can provide controllable point defects, allows us to produce a controlled defect driven true super-tetragonal (T) phase with a single-domain-state in ferroelectric BiFeO3 thin films. This point-defect engineering is found to drive the phase transition from the as-grown mixed rhombohedral-like (R) and tetragonal-like (MC ) phase to true tetragonal (T) symmetry and induce the stripe multi-nanodomains to a single domain state. By further increasing the injected dose of the He ion, we demonstrate an enhanced tetragonality super-tetragonal (super-T) phase with the largest c/a ratio of ∼1.3 that has ever been experimentally achieved in BiFeO3 . A combination of the morphology change and domain evolution further confirms that the mixed R/MC phase structure transforms to the single-domain-state true tetragonal phase. Moreover, the re-emergence of the R phase and in-plane nanoscale multi-domains after heat treatment reveal the memory effect and reversible phase transition and domain evolution. Our findings demonstrate the reversible control of R-Mc-T-super T symmetry changes (leading to the creation of true T phase BiFeO3 with enhanced tetragonality) and multidomain-single domain structure evolution through controllable defect engineering. This work also provides a pathway to generate large tetragonality (or c/a ratio) that could be extended to other ferroelectric material systems (such as PbTiO3, BaTiO3 and HfO2 ) which might lead to strong polarization enhancement.